Assessing the Association between Leptin and Bone Mineral Density in HIV-Infected Men - Madhu N. Rao; Morris Schambelan; Viva W. Tai; Donald I. Abrams; Hootan Khatami; Peter J. Havel; Giorgos Sakkas; Kathleen Mulligan (AIDS Research and Treatment)
HIV-infected individuals are at risk for decreased bone mineral density (BMD). The known risk factors for bone loss do not fully explain the increased risk in this population. There is emerging evidence that leptin, a hormone secreted by adipocytes, plays an important role in bone metabolism. Several studies have assessed the relationship between leptin and bone density in healthy adults, but there are few such studies in HIV-infected individuals. Furthermore, HIV infected individuals on antiretroviral therapy are at increased risk for altered fat distribution, which may impact the relationship between leptin and BMD. In a cross-sectional analysis of data in 107 HIV-infected men, we determined whether serum leptin levels were associated with whole-body BMD and bone mineral content measured by dual-energy X-ray absorptiometry (DEXA), after adjusting for confounders including body fat distribution. We found an inverse association between leptin and bone density in those with peripheral lipoatrophy, defined objectively as <3 kg appendicular fat by DEXA, but no such relationship was seen in those with >3 kg appendicular fat. This result suggests that fat distribution may modify the relationship between leptin and bone density.